Uang Pannai in the Bugis Marriage Custom: Islamic Legal Perspective on Local Traditions - Haif, Abu; Nisa, Andi Muzizatun; Mubarak, Syahrum; Herman, M Aras; Fausya, Annisa (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This research aims to analyze the practice of uang pannai in Bugis marriage customs and examine the perspective of Islamic law on this local tradition. This research is important because the escalation of the value of the “uang pannai“ has created an economic burden that prevents young couples from marrying, resulting in a shift from the original philosophical meaning of the tradition that emphasizes honor and reward. This phenomenon requires harmonization between local cultural practices and Islamic values in the context of a multicultural society. The research method used is qualitative with a descriptive-analytical approach through literature studies, using primary data from the Quran, hadith, and classical and contemporary fiqh literature, as well as secondary data from relevant books, scientific journals, and previous research. The results of the study show that uang pannai ' has a deep social meaning in the Bugis society as a symbol of honor, an instrument of social status affirmation, and a medium for family unification. From the perspective of Islamic law, this tradition is acceptable as long as it does not conflict with sharia principles, especially when evaluated through the framework of sharia maqasid. The research concludes that the harmonization between the tradition of uang panai' and Islamic values can be achieved through moderation in the determination of amounts, emphasis on symbolic meaning, and integration with dowry, so that cultural heritage is maintained while maintaining conformity with Islamic teachings.